Empowering Social Science Research in the Big-Data Era: Addressing Quantyphobia in IR Researches - Farizal Mohd Razalli (Center for Southeast Asian Social Studies (CESASS), 2019)
This paper tries to explore the employment of quantitative approach in political researches focusing on international relations (IR) or international politics. A debate emerged in the90s on whether IR or the field of international politics should be driven by quantitative(positivistic) approach at the expense of qualitative (interpretivist) approach. The debate then expanded to explicitly argue for an increased use of formal methods that are mathematically-based to study IR phenomena. It triggered then a quick reaction fromhardcore IR specialists who warned against mathematizing IR for fear of turning the field into a mechanical field that crunches numbers. Such a fear is further substantiated by theobservation that many quantitative works in IR have moved farther away from developing theory to testing hypotheses. Some scholars have even suggested that it is epistemologicallyrealism vs. instrumentalism; something that is unsurprising given the dominance of realism inIR for many years. This paper does not suggest that heavy emphasis on qualitative approach leads to a inferior research output. However, it does suggest an transformative incapability among IR scholars to accommodate to contemporary global changes. The big-data analyticshave affected the intellectual community of late with the influx of data. These data are bothqualitative and quantitative. Nonetheless, analyzing them requires one to be familiar with quantitative methods lest one risks not being able to offer a research outcome that is not only sound in its argumentation but also robust in its analytical logic. Furthermore, with so much data on the social media, it is almost unthinkable for meaningful interpretation tobe made without even the simplest descriptive statistical methods. The key findings revealthat in ensuring its relevance, international political researches have to start adapting to the contemporary changes by building new capability apart from upscaling existing capacity.